Pengaruh Gamifikasi Triangle Cone terhadap Kemampuan Gerak Lokomotor Siswa Kelas 6 di SDN Barata Jaya - Edwin Dwi Ainul Yaqin; Muchamad Arif Al Ardha (MAN Insan Cendekia Jambi, 2026)
The study aimed to analyze the effect of Triangle Cone gamification on the locomotor movement skills of sixth-grade students at SDN Barata Jaya. A quantitative approach was employed using a quasi-experimental method with a non-equivalent control group design. The participants consisted of 54 students divided into an experimental group (n = 27) and a control group (n = 27). The experimental group received PJOK instruction based on Triangle Cone gamification, while the control group was taught using conventional methods. Fundamental movement skills were assessed using the MOBAK 5–6 instrument, covering the domains of self-movement and object movement. Data analysis was conducted through descriptive statistics, the Shapiro–Wilk normality test, and the Mann–Whitney U test. The results revealed a significant difference between the two groups (p = 0.000 < 0.05). The mean improvement score of the experimental group (M = 1.04) was higher than that of the control group (M = –1.11). These findings indicate that the implementation of Triangle Cone gamification effectively enhances coordination, agility, movement control, and active student engagement in learning. The integration of structured, competitive, and collaborative game elements provides meaningful movement experiences and supports the optimal development of elementary students’ motor competencies compared to conventional approaches.